Evaluation of the loop mediated isothermal DNA amplification (LAMP) kit for malaria diagnosis in P. vivax endemic settings of Colombia. - Andrés F Vallejo; Nora L Martínez; Iveth J González; Myriam Arévalo-Herrera; Sócrates Herrera (Public Library of Science (PLoS), 2015)
Most commonly used malaria diagnostic tests, including microscopy and antigen-detecting rapid tests, cannot reliably detect low-density infections which are frequent in low transmission settings. Molecular methods such as polymerase chain reaction (PCR) are highly sensitive but remain too laborious for field deployment. In this study, the applicability of a malaria diagnosis kit based on loop-mediated isothermal amplification (mLAMP) was assessed in malaria endemic areas of Colombia with Plasmodium vivax predominance.First, a passive case detection (PCD) study on 278 febrile patients recruited in Tierralta (department of Cordoba) was conducted to assess the diagnostic performance of the mLAMP method. Second, an active case detection (ACD) study on 980 volunteers was conducted in 10 sentinel sites with different epidemiological profiles. Whole blood samples were processed for microscopic and mLAMP diagnosis. Additionally RT-PCR and nested RT-PCR were used as reference tests. In the PCD study, P. falciparum accounted for 23.9% and P. vivax for 76.1% of the infections and no cases of mixed-infections were identified. Microscopy sensitivity for P. falciparum and P. vivax were 100% and 86.1%, respectively. mLAMP sensitivity for P. falciparum and P. vivax was 100% and 91.4%, respectively. In the ACD study, mLAMP detected 65 times more cases than microscopy. A high proportion (98.0%) of the infections detected by mLAMP was from volunteers without symptoms.mLAMP sensitivity and specificity were comparable to RT-PCR. LAMP was significantly superior to microscopy and in P. vivax low-endemicity settings and under minimum infrastructure conditions, it displayed sensitivity and specificity similar to that of single-well RT-PCR for detection of both P. falciparum and P. vivax infections. Here, the dramatically increased detection of asymptomatic malaria infections by mLAMP demonstrates the usefulness of this new tool for diagnosis, surveillance, and screening in elimination strategies.